Biomolecular changes and DNA targeting effect of sesamol in human lung adenocarcinoma (SK-LU-1) cells by FTIR microscopy - Boondaree Siriwarin; Natthida Weerapreeyakul; Waraporn Tanthanuch; Kanjana Thumanu (Asian Pacific Journal of Tropical Biomedicine, 2018)
Objective: To investigate biomolecular alteration of sesamol on human lung adenocarcinoma (SK-LU-1) cells compared with cisplatin using Fourier transform infrared microscopy (FTIR). Methods: Cytotoxicity of sesamol was investigated against SK-LU-1 cells by using neutral red. DNA fragmentation and the cell cycle analysis were determined by agarose gel electrophoresis and flow cytometry, respectively. The FTIR microscopy technique was applied to explore the changes in cellular biochemical compositions in cells treated with sesamol that the biochemical and biological assays cannot cover. The alkylating property was determined by 4-(4-nitrobenzyl)pyridine assay. Results: Sesamol and cisplatin exerted an antiproliferative effect at 48 h with respective IC50 values of 2.7 and 0.07 mM. Both induced apoptosis by causing DNA damage and accumulation of cell populations at sub-G1. FTIR microscopy and Principle Component Analysis clearly discriminated the sesamol- and cisplatin-treated cells from the untreated cells or control. A significant increase of total lipid content was found in cisplatin-treated cells. Conformational changes in the proteins secondary structure from the α -helix to the β -sheet were found in both sesamol- and cisplatin-treated cells, as well as significant reductions in relative DNA content of both compared to the control were observed, suggesting DNA damage. A shift in the peak position of DNA region provides insight on the DNA interactions. Conclusions: The non-alkylating effect of sesamol based on the nitrobenzyl pyridine assay delineates the non-covalent binding mode of sesamol on DNA. Hydrogen bonding is the binding mode of sesamol on DNA, while for cisplatin it was covalent and hydrogen bonding.